Rifaximin for the treatment of irritable bowel syndrome – a drug safety evaluation. Issue 7 (2nd July 2016) - Ponziani, Francesca Romana; Pecere, Silvia; Lopetuso, Loris; Scaldaferri, Franco; Cammarota, Giovanni; Gasbarrini, Antonio
ABSTRACT: Introduction: Irritable bowel syndrome is a functional gastrointestinal disorder with a multifactorial etiology. Alterations of intestinal motility and immunity, gut-brain interactions, as well as gut microbiota dysbiosis contribute to the development of irritable bowel syndrome. Therefore, gut microbiota modulation by non-absorbable antibiotics is a therapeutic option in patients with IBS. Areas covered : Published articles including patients with irritable bowel syndrome reporting data about rifaximin activity and safety have been searched throughout the literature and selected. Expert opinion: The optimal antibiotic molecule should be local-acting, long-acting and safe-acting. Rifaximin is a non-absorbable antibiotic with additional anti-inflammatory and gut microbiota-modulating activity. It is effective in inducing symptoms relief in patients with IBS, even after repeated treatment courses. Rifaximin-related side effects in patients with IBS are reported to be mild and infrequent; microbial resistance is rare and transient, due to the high local concentration of the drug and to the absence of horizontal transmission. Clostridium difficile infection is not usual in patients receiving rifaximin in absence of predisposing conditions such as hospitalization and immunosuppression, which are uncommon in patients affected by irritable bowel syndrome. Nevertheless rifaximin is an antibiotic active against Clostridium difficile infection. Rifaximin has limited metabolic interactions and is not expected to interfere with drug metabolism in patients with normal hepatic function. These properties make rifaximin a safe antibiotic for gut microbiota modulation in patients with IBS.